(untitled) (Journal of Medicine, 2014)
Sturge-Weber syndrome is a rarenon-hereditary condition characterized by a hamartomatous vascular proliferation. It is usually unilateral; bilateral involvement is seen only in 15% cases. We report a case of a 6 month old male child with Sturge-Weber syndrome with its inherent clinical features and typical imaging findings. DOI: http://dx.doi.org/10.3329/jom.v15i1.19877 J Medicine 2014; 15: 68-70